Optimizing Trade Secret Criminal Law Policies in Indonesia: Lessons from the United States - Ratna Kumala Sari; Khilmatin Maulidah (Universitas Internasional Batam, 2023)
The acceleration of global free trade necessitates high-quality product outcomes, driving the creation of technology to meet these demands. Consequently, the significance of Intellectual Property Rights in advancing technological developments becomes increasingly apparent. In the realm of commerce, competition is inherent and vital to attain objectives, which include acquiring consumers and maximizing profits. Unfortunately, such competition often leads to fraudulent practices and ensuing conflicts. To mitigate and address unfair competition, it is imperative to establish regulations that entrepreneurs and business entities must adhere to, both preventively and punitively. This study seeks to analyze the current and prospective criminal law policy regarding trade secret offenses within the existing legal framework. The research employs a normative legal approach. The findings reveal that trade secret offenses in Indonesia are governed by Law Number 30 of 2000, but it exhibits certain weaknesses and shortcomings. The proposed Trade Secrets Bill aims to adapt to international standards, fostering economic benefits while maintaining legal protection convergence.